Rainfall Erosivity Factor Update in Uruguay - Pérez Bidegain, Mario; Piaggio, Juan Manuel; Baethgen, Walter; García Préchac, Fernando (Agrociencia Uruguay, 2017)
The Universal Soil Loss Equation (USLE) and its revised form (RUSLE) are the soil erosion models incorporated into the EROSION 6.0 software. This, in turn, is the soil conservation planning tool used to fulfill the soil conservation regulations in Uruguay. The objective of this technical note was to use the methodology proposed by Renard and Freimund (1994) to update the rainfall erosivity factor (R factor) values incorporated into the EROSION 6.0 software. Additionally, it had the following specific objectives: to evaluate the impact of the length of the rainfall data series on the estimation of the R factor and to compare the updated values to the ones that are currently used. The rainfall data base used to estimate the R factor comprises the 1980-2009 period in different Uruguay locations. The equations used in this work allowed to update the R factor, and to obtain R factor values that agree with published R values for the region. The regression line intercept and slope between the 30 yr R factor estimated by both equations did not differ from zero (P < 0.29), and one (P < 0.70), respectively. The length of rainfall data series affects the R factor value, given the high interannual rainfall variability. We recommend using R factors based on 30 years of pluviometric records.